The Influence of Ionic Environment and Histone Tails on Ordered Columnar Phases of Nucleosome Core Particles - Berezhnoy, Nikolay V. (2016)
The nucleosome core particle (NCP) is the basic building block of chromatin. Nucleosome-nucleosome interactions are instrumental in chromatin compaction, and understanding NCP self-assembly is important for understanding chromatin structure and dynamics. Recombinant NCPs aggregated by multivalent cations form various ordered phases that can be studied by x-ray diffraction (small-angle x-ray scattering). In this work, the effects on the supramolecular structure of aggregated NCPs due to lysine histone H4 tail acetylations, histone H2A mutations (neutralizing the acidic patch of the histone octamer), and the removal of histone tails were investigated. The formation of ordered mainly hexagonal columnar NCP phases is in agreement with earlier studies; however, the highly homogeneous recombinant NCP systems used in this work display a more compact packing. The long-range order of the NCP columnar phase was found to be abolished or reduced by acetylation of the H4 tails, acidic patch neutralization, and removal of the H3 and H2B tails. Loss of nucleosome stacking upon removal of the H3 tails in combination with other tails was observed. In the absence of the H2A tails, the formation of an unknown highly ordered phase was observed.